About synthesis mechanism of periodic oxide nanocrystallites on surface of single-crystal InP - Kovachov, S.; Bohdanov, I.; Bardus, I.; Drozhcha, D.; Tikhovod, K.; Khrekin, A.; Bondarenko, V.; Kosogov, I.; Suchikova, Y. (Physics and Chemistry of Solid State, 2023)
We have obtained unique periodic oxide nanocrystallites on the surface of indium phosphide. The morphological characteristics of the structures obtained and their component composition are investigated in the article. The main attention is focused on explaining the mechanism of the periodic structures, which are packed by the ‘parquet floor’ type. The mechanism based on sliding the sources of rectangular-shaped dislocation loops has been proposed. The system of the main and secondary (ingoing) dislocations that cause the formation of the steps has been considered. The mathematical interpretation of the described model has also been proposed.